PENGARUH PELATIHAN DAN KOMUNIKASI INTERNAL TERHADAP KINERJA KARYAWAN BAGIAN ADMINISTRASI PT. PLN (PERSERO) AREA PEKANBARU - Safitri, Siska Widia; ", Suryalena (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
PT. PLN (Persero) Pekanbaru Area is one of the branches of PT. PLN (Persero) Riau and Riau Islands Region. PT. PLN (Persero) Pekanbaru Area is one of the State-Owned Enterprises (BUMN). PT. PLN (Persero) Pekanbaru Area is located at JL. Dr. SetiaBudhi No 57, Rintis, LimaPuluh, Pekanbaru City. PT. PLN (Persero) Pekanbaru Area conducts training and internal communication is expected to be able to encourage morale and also improve employee performance.               In this research the methodology used is descriptive, quantitative which is collected through a questionnaire method of 42 respondents. The samples used were employees of PT. PLN (Persero) Pekanbaru Area and as a source of information is HRD to determine the sample used the census method.               The results of the research and hypothesis testing showed that the training had a significant effect on employee performance in the Office Section of PT. PLN (Persero) Pekanbaru Area. And internal communication has a significant effect on the performance of employees of PT. PLN (Persero) Pekanbaru Area. The training and internal communication variables simultaneously have a significant effect on the performance of the employees of PT. PLN (Persero) Pekanbaru Area. Keywords: Training, Internal Communication, Employee Performance Administration Section PT. PLN (Persero) Pekanbaru Area.